2009
DOI: 10.1007/s00268-009-0284-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Compression Versus Subcutaneous Heparin Therapy in Postoperative and Posttrauma Patients: A Systematic Review and Meta‐Analysis

Abstract: These results suggest that the overall bleeding risk profile favors the use of compression over heparin, with the benefits in term of venous thromboembolic disease prophylaxis being similar between groups. Subgroup analyses suggest that low molecular weight heparin may have a differential effect; this observation should be further evaluated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 41 publications
(44 reference statements)
1
44
0
3
Order By: Relevance
“…28 Studies compared heparin with IPC (nine studies), foot pump (four studies), or ES (three studies). Sample sizes ranged from 51 to .…”
Section: Ivc Filter Vs No Ivc Filtermentioning
confidence: 99%
“…28 Studies compared heparin with IPC (nine studies), foot pump (four studies), or ES (three studies). Sample sizes ranged from 51 to .…”
Section: Ivc Filter Vs No Ivc Filtermentioning
confidence: 99%
“…Indirect evidence from various orthopedic and nonorthopedic surgical populations was provided in a recent meta-analysis by Eppsteiner of 16 trials (3,887 patients) of various compression modalities tested against LDUH or LMWH. 51 Pooled results for mechanical compression compared with heparin failed to show or to exclude a benefi cial or detrimental effect for DVT (RR, 1.07; 95% CI, 0.72-1.61) or PE (RR, 1.03; 95% CI, 0.48-2.22). Mechanical compression was associated with a reduced risk of postoperative bleeding compared with heparin (RR, 0.47; 95% CI 0.31-0.70).…”
Section: Mechanical Compression Vs Heparinmentioning
confidence: 99%
“…51 However, as subgroup analysis in that meta-analysis suggested that LMWH may be more effective than compression, and taking into account that the baseline rate of bleeding is lower among medical patients (average from RCTs, 0.4%) than surgical patients, if the bleeding risk is temporary and if patients remain at high risk of VTE ( Table 2 ), pharmacologic thromboprophylaxis should be initiated once the bleeding risk has decreased.…”
Section: Mechanical Compression and Pharmacologicmentioning
confidence: 99%
“…In addition, foot pumps were never reported to be utilized in the region. The effectiveness of mechanical VTE prophylaxis alone or in combination with pharmacologic prophylaxis has been shown in many studies to be the recommended method in high-risk patients as published in guidelines [12,16,17,18]. Mechanical prophylaxis was rarely used in high-risk patients in this study.…”
Section: Discussionmentioning
confidence: 91%